Interactions humaines et théorie des catastrophes : une application au comportement du vacancier - Vermot-Desroches, Bernard (L'Actualité économique, 1981)
ABSTRACTExamination of recent information about tourist journeys outside Quebec Province has given rise to the idea that such trips do not take place in accordance with conventional laws such as those based on the universal gravitation model, but rather are governed by criteria of decision in which distance is not a continuous variable. After emphasizing certain weaknesses of conventional models of spatial interaction, this article shows that the theory of catastrophes, developed from R. Thom's studies of morphogenesis, makes possible a new approach, based on utilitarian concepts, to the role played by distance in tourist journeys.